2018
DOI: 10.18632/oncotarget.25307
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the promoter region of the CRBN gene as a predictive factor for the first-line CTD therapy in multiple myeloma patients

Abstract: Cereblon is a primary molecular target for immunomodulatory drugs. The aim of this study was to evaluate the influence of selected clinical and molecular factors including single nucleotide polymorphisms (SNPs) in CRBN gene on the efficacy of first line CTD (cyclophosphamide, thalidomide, dexamethasone) chemotherapy in patients with multiple myeloma. Study group consisted of 68 patients. Analysis of CRBN gene SNPs (rs6768972, rs1672753) was performed using Real-Time PCR genotyping technique. Median progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…GWAS reveal, however, almost 90% of disease-associated variants are located outside protein coding regions 11 , and this combined with advancing NGS technologies are promoting studies into regulatory variants and their impact on regulatory elements 25 . The few germinative CRBN variants that have been linked to thalidomide responsiveness in treatment of MM are found in regulatory regions [26][27][28] . Indeed, in a microarray of more than 300,000 exonic SNPs performed in MM patients treated with a chemotherapy scheme comprising thalidomide and bortezomib, no significance was found in the presence of any variant 29 .…”
Section: Discussionmentioning
confidence: 99%
“…GWAS reveal, however, almost 90% of disease-associated variants are located outside protein coding regions 11 , and this combined with advancing NGS technologies are promoting studies into regulatory variants and their impact on regulatory elements 25 . The few germinative CRBN variants that have been linked to thalidomide responsiveness in treatment of MM are found in regulatory regions [26][27][28] . Indeed, in a microarray of more than 300,000 exonic SNPs performed in MM patients treated with a chemotherapy scheme comprising thalidomide and bortezomib, no significance was found in the presence of any variant 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This gene is extremely conserved and a few polymorphism was found in the coding region 23,32 . Studies performed with MM showed that polymorphisms in non-coding regions of CRBN were associated with response to thalidomide and others IMIDs therapy 20,21,29 .…”
Section: Discussionmentioning
confidence: 99%
“…CRBN gene encodes a protein 442 amino acids long, has 11 exons (NM_016302) and is highly conserved, hence, polymorphisms in its coding regions are rare. Therefore, some studies have analyzed non-coding regions of the gene that may be associated with the control of gene expression [20][21][22] . Three variants that ank the exons encoding the thalidomide-binding region of CRBN have been identi ed by bioinformatics tools as possible modulators of splicing sites with the potential to affect either the expression or activity of the protein 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the CRBN AA genotype (rs6768972) was correlated with the extension of median progression‐free survival (PFS; 18 vs. 9 months; Hazard ratio = 0·49, P = 0·0062). Significantly shorter median PFS was noted in patients with the CRBN CC genotype (rs1672753) (4 vs. 16 months, Hazard ratio = 3·93, P = 0·0321) (Szudy‐Szczyrek et al , ).…”
Section: Discussionmentioning
confidence: 99%